IMPLEMENTATION OF THE IMPORTANCE PERFORMANCE ANALYSIS METHOD IN MEASURING SOLID WASTE MANAGEMENT PERFORMANCE IN SENDAWAR CITY, WEST KUTAI REGENCY - Cahya, Fajar Nur (ASEAN Journal of Systems Engineering, 2025)
Solid waste management is a public service that must be provided by the government and regulated by law. The Solid waste management service in Sendawar City is currently managed by the local government through the Environmental Government Agency (DLH) of West Kutai Regency. In the service business, an evaluation process is needed in order to know the extent to which the level of performance has been achieved, especially from the point of view of service users. In this study, the method used to evaluate the solid waste management service in Sendawar City is the Importance Performance Analysis (IPA), using five service quality variables, namely reliability, assurance, tangibles, empathy, and responsiveness. Then, five variables are translated into twenty attributes as evaluation material from the service user community.The results of this study found that the level of conformity between the level of performance and the level of importance in the solid waste management system in the City of Sendawar was 78.32% ( good category), definitively meaning that the user community considered the performance of DLH was good, although there were several attributes that, according to the community should be a priority for improvement because they are deemed not optimal, namely the BF2 attribute (availability of garbage bins (TPS) and equipment for transporting garbage), BF4 attribute (safety and health equipment for transport officers) and the DT3 attribute (readiness and responsiveness of the Department in responding to public complaints).